THE EFFECT OF JOB SATISFACTION, ORGANIZATIONAL COMMITMENT, AND LEADERSHIP ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR EMPLOYEES OF BRI IN YOGYAKARTA - Syaflinursyah, Aulia; Aktif, Nur (Dinasti Publisher, 2020)
Organizational citizenship behavior is important for the success of an organization because basically organizations cannot directly anticipate and improve all behavior in organizations simply by relying on formally instructed job descriptions. This study aims to examine and analyze the effect of job satisfaction, organizational commitment, and leadership on organizational citizenship behavior of BRI employees in Yogyakarta. The study used a quantitative approach with multiple linear regression quantitative analysis methods using SPSS 25.0. The number of samples taken in this study was 83 respondents using the saturated sampling method. Research result shows that (1) there is an effect of job satisfaction on organizational citizenship behavior, (2) there is an effect of organizational commitment on organizational citizenship behavior, (3) there is an effect of leadership on organizational citizenship behavior, (4) there is an effect of job satisfaction, organizational commitment, and leadership on organizational citizenship behavior simultaneously.